A Case on Problems in Quality and Reasons in Rice -Under the Scheme of UPDS in Tamil Nadu - A, Mahendran (Asian Journal of Agriculture and Rural Development, 2013)
The annual subsidy for the Universal PDS in Tamil Nadu was around 5,000crore, and adding that there was a strong administrative monitoring, vigilance and grievance redresses mechanism operating in the state in respect of UPDS. But the quality of rice distributed through the universal pubic distribution system under the free of cost as on 01 June 2011 scheme was of poor quality and unfit for consumption by the public in the state. Also the price of essential commodities such as Pulses, groceries such as cooking oil and chili powder and vegetables had gone up. As the rice bags were stored by the TNCSC in open granaries, they were exposed to the elements. According to public assessment, the quality of PDS rice was not satisfactory, but it was fair quality rice, as per the Food Corporation of India’s standard. But this case focuses on why rice is poor quality and processing paddy to rice methods, value added rice, and some other issues in Universal PDS in the state.